2020
DOI: 10.3390/ijms21218160
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Archived Tissue of Primary Melanoma Identifies Proteins Associated with Metastasis

Abstract: Formalin-fixed paraffin embedded (FFPE) clinical tissues represent an abundant and unique resource for translational proteomic studies. In the US, melanoma is the 5th and 6th most common cancer in men and women, respectively, affecting over 230,000 people annually and metastasising in 5–15% of cases. Median survival time for distant metastatic melanoma is 6–9 months with a 5-year-survival of < 15%. In this study, 24 primary FFPE tumours which have metastasised (P-M) and 24 primary FFPE tumours which did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Studies such as these give the groundwork for further developing our understanding of melanoma progression, the pathways and biological processes potentially affected at each stage as well as subtype, and biomarkers for clinical use. 49 ; while only four studies include benign naevi, 50,51 dysplastic naevi 52 and melanoma in situ. 53 Moreover, the use of formalin-fixed paraffin-embedded (FFPE) samples as a reliable source of material for proteomic investigations had only been recently demonstrated.…”
Section: Proteomi C S and Its P Otential To Un Cover Differentiating ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies such as these give the groundwork for further developing our understanding of melanoma progression, the pathways and biological processes potentially affected at each stage as well as subtype, and biomarkers for clinical use. 49 ; while only four studies include benign naevi, 50,51 dysplastic naevi 52 and melanoma in situ. 53 Moreover, the use of formalin-fixed paraffin-embedded (FFPE) samples as a reliable source of material for proteomic investigations had only been recently demonstrated.…”
Section: Proteomi C S and Its P Otential To Un Cover Differentiating ...mentioning
confidence: 99%
“…A comprehensive review by Sengupta and colleagues (2016) 48 reported on 25 proteomic studies contributing to melanoma research from 2011 to 2016. Most studies have focussed on metastatic melanoma (Table 2), for example, Shapanis (2020) 49 ; while only four studies include benign naevi, 50,51 dysplastic naevi 52 and melanoma in situ 53 . Moreover, the use of formalin‐fixed paraffin‐embedded (FFPE) samples as a reliable source of material for proteomic investigations had only been recently demonstrated 54–58 .…”
Section: Proteomics and Its Potential To Uncover Differentiating Biom...mentioning
confidence: 99%